Improving Employees’ Performance Through Work Environment, Leadership, And Organization Culture To Create Work Satisfaction At Pt. Sukun, Kudus - - Sukirman (Conference In Business, Accounting, And Management (CBAM), 2012)
The purpose of this study is to analyze the impact of work environment, leadership, and organization culture toward work satisfaction of employees; to analyze the impact of work environment, leadership, and organization culture toward the performance of employees; to analyze the impact of work satisfaction toward the performance of employees at PT. SUKUN, Kudus. The population number of this study consisted of 436 employees at PT. SUKUN, Kudus. Sample of 120 respondents were taken by using a purposive sampling method. Data were collected by using questionnaires and analyzed by using causality model. Hypotheses were tested by using a Structural Equation Model (SEM) of AMOS program. Based on the result of data analysis, it was known that work environment, leadership, and organization culture had a significant impact toward work satisfaction of employees. Work environment had a significant and positive impact toward employees’ performance and had a significant and indirect impact toward the employees’ satisfaction. Leadership had a significant and indirect impact toward the employees’ performance. Organization culture did not have any significant impact, but it had a significant and indirect impact through employees’ work satisfaction. Employees’ work satisfaction had a significant and positive impact toward the employees’ performance.Key words: Work environment, leadership, organization culture, work satisfaction, and employees’ performance.